Forecasting of Vegetable Production in Haryana by Ordinary Least Square Method and ARIMA Model (Indian Journal of Extension Education, 2022)
India has the world’s second-largest production of fruit and vegetables. In India, a variety of agro-climate zones with unique seasons allow for the cultivation of a diverse range of vegetables. From this study, it was attempted to estimate the production of vegetables in the upcoming year through means of ordinary least squares (OLS) method and ARIMA (Autoregressive Integrated Moving Average) model using secondary data. This study is based on time series data of vegetables from 1990-91 to 2020-21 in open field condition, which was taken from National Horticulture Board (NHB) website, while the area and production reports on cultivation of vegetables from the Horticulture Department, Haryana state of India. In the current context, it was fetched out that the forecasted value of the vegetables production for the year 2021-22 will be 7540814.31 tonnes in open field condition. Further, for predicting the area and production of vegetables in Haryana, ARIMA (1, 2, 1) was fitted after experimenting with various lags of the moving average and autoregressive procedures.